Virus-like particle vaccines - Mukhopadhyay, E; Hill, AVS; Salman, AM (Academic Press, 2022)
Vaccines are among the most successful and cost-effective public health tools for preventing infectious diseases and death. Virus-like particles (VLPs) have made impressive progress in the field of vaccinology over the last three decades so that several VLP-based vaccines are commercially available and generating great public health impact, for example, the hepatitis B virus and the human papillomavirus (HPV) vaccines or in advanced clinical trials such as the RTS,S and R21 VLP malaria vaccines. We have growing in-house experience in Oxford of the use of a wide range of VLPs to target malaria and other diseases by vaccination. As VLPs lack genetic material, they have no replication capacity and are considered very safe. Additionally, VLP-based vaccines have significant ability to induce both innate and adaptive immune responses as well as being safe templates with favorable low-cost and large-scale manufacturing available.